2021
DOI: 10.3390/jof7090685
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of a Biocontrol Agent Trichoderma asperellum SC012 and Hymexazol Reduces the Effective Fungicide Dose to Control Fusarium Wilt in Cowpea

Abstract: The use of synthetic fungicide needs to be gradually reduced because of its adverse effect on human health and the environment. An integrated approach combining fungicides with biological control agents (BCAs) can be used to reduce the fungicide doses, thereby minimizing the risks associated with chemical fungicides. In this study, the combined application of a BCA Trichoderma and a fungicide hymexazol was used to manage the cowpea wilt disease caused by Fusarium oxysporum. The Trichoderma SC012 strain, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 44 publications
(46 reference statements)
1
24
0
2
Order By: Relevance
“…In addition, conventional fungicides can reduce the pathogenicity of fungi, thus making it easier for plants to induce resistance against fungi and reducing the amount and frequency of chemical fungicide applications (Oostendorp et al, 2001). Zhang et al (2021b) found that compared with Trichoderma asperellum SC012 and hymexazol alone, combined application can Relative abundances of the main soilborne fungi in the different treatments. Screening of relative abundances of major soilborne fungal genera in wheat at the fungal genus level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, conventional fungicides can reduce the pathogenicity of fungi, thus making it easier for plants to induce resistance against fungi and reducing the amount and frequency of chemical fungicide applications (Oostendorp et al, 2001). Zhang et al (2021b) found that compared with Trichoderma asperellum SC012 and hymexazol alone, combined application can Relative abundances of the main soilborne fungi in the different treatments. Screening of relative abundances of major soilborne fungal genera in wheat at the fungal genus level.…”
Section: Discussionmentioning
confidence: 99%
“…Hymexazol (HYM), to which Aphanomyces and Pythium are sensitive to, is a systemic chemical fungicide that is used against a broad spectrum of soil-borne fungi and was developed by Sankyo Co., Ltd. in the 1960s. , HYM can inhibit spore germination of fungi by combining aluminum and iron ions in the soil or can interfere with the RNA and DNA biosynthesis of pathogenic fungi to control diseases in vitro . Additionally, HYM can be directly absorbed by plant roots and metabolized quickly into two glycoside metabolites (Figure ), an N -connection hymexazol glucoside, 2-(β- d -glucopyranosyl)-5-methyl-4-isoxazoline-3-one, and an O -connection hymexazol glucoside, 3-(β- d -glucopyranosyl)-5-methylisoxazole.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 HYM can inhibit spore germination of fungi by combining aluminum and iron ions in the soil or can interfere with the RNA and DNA biosynthesis of pathogenic fungi to control diseases in vitro. 14 Additionally, HYM can be directly absorbed by plant roots and metabolized quickly into two glycoside metabolites (Figure 1), an N-connection hymexazol glucoside, 2-(β-D-glucopyranosyl)-5-methyl-4-isoxazoline-3-one, and an O-connection hymexazol glucoside, 3-(β-D-glucopyranosyl)-5-methylisoxazole. Interestingly, HYM O-glucoside has a weaker antifungal activity than HYM, and N-glucoside even has no antifungal ability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is reported that Trichoderma played an important role in reducing the adverse effects of salt stress in the desert shrub Ochradenus baccatus [16]. Trichoderma can be used to control plant disease mainly due to their antagonistic and mycoparasitic activity [17][18][19]. Also, they can enhance nutrients absorption of plant [20] and promote the production of numerous biochemical elicitors, including all kinds of peroxidases (PODs), chitinase, β-1,3-glucanase, lipoxygenase-pathway hydroperoxide lyase, and compounds such as phytoalexins and phenols, thereby promoting growth and enhancing biotic and abiotic stress tolerance of plants [21][22][23].…”
Section: Introductionmentioning
confidence: 99%